2016
DOI: 10.1021/acs.est.6b03492
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Chemicals in an Urban Population of Pregnant Women and Their Newborns from San Francisco

Abstract: Exposures to environmental pollutants in utero may increase the risk of adverse health effects. We measured the concentrations of 59 potentially harmful chemicals in 77 maternal and 65 paired umbilical cord blood samples collected in San Francisco during 2010-11, including polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), polybrominated diphenyl ethers (PBDEs), hydroxylated PBDEs (OH-PBDEs), and perfluorinated compounds (PFCs) in serum, and metals in whole blood. Consistent with previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 45 publications
5
81
2
1
Order By: Relevance
“…Because they can be present in significant quantities in products (5–30% by weight) ( Darnerud et al 2001 ; World Health Organization 1994 ) and because they are additives rather than covalently bound to consumer products, there is higher potential for leaching, volatilization, or degradation, leading to consumer and environmental exposures ( Darnerud et al 2001 ; Gill et al 2004 ; Watanabe and Sakai 2003 ). Human exposures are ubiquitous beginning in utero ( Morello-Frosch et al 2016 ; Woodruff et al 2011b ), which is a highly vulnerable period of human brain development ( Grandjean et al 2008 ), and PBDEs have been found pervasively in U.S. household dust samples ( Darnerud et al 2001 ; Frederiksen et al 2009 ; Mitro et al 2016 ). Levels of PBDEs measured in Americans are the highest in the world, due to greater historic use of these chemicals in the U.S. than elsewhere because of differences in regulatory standards across countries ( Besis and Samara 2012 ; Frederiksen et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because they can be present in significant quantities in products (5–30% by weight) ( Darnerud et al 2001 ; World Health Organization 1994 ) and because they are additives rather than covalently bound to consumer products, there is higher potential for leaching, volatilization, or degradation, leading to consumer and environmental exposures ( Darnerud et al 2001 ; Gill et al 2004 ; Watanabe and Sakai 2003 ). Human exposures are ubiquitous beginning in utero ( Morello-Frosch et al 2016 ; Woodruff et al 2011b ), which is a highly vulnerable period of human brain development ( Grandjean et al 2008 ), and PBDEs have been found pervasively in U.S. household dust samples ( Darnerud et al 2001 ; Frederiksen et al 2009 ; Mitro et al 2016 ). Levels of PBDEs measured in Americans are the highest in the world, due to greater historic use of these chemicals in the U.S. than elsewhere because of differences in regulatory standards across countries ( Besis and Samara 2012 ; Frederiksen et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory measurements: Blood samples were processed within hours of collection, and the separated serum stored at −20 • C until analysis. Laboratory methods for the measurement of serum levels of PBDEs, PFASs, and PCBs were described previously [13,16,40]. Briefly, PCBs and PBDEs were measured using automated solid-phase extraction (SPE) and gas chromatography (GC)/high-resolution mass spectrometry (HRMS); PFASs were measured using an online SPE-liquid chromatography-tandem MS (SPE-LC-MS/MS) method.…”
Section: Methodsmentioning
confidence: 99%
“…(Median concentration and IQR, presented in ng g −1 lipid). Cord serum to maternal serum, (R cm , lipid adjusted) Placenta to maternal serum, (R pm , lipid adjusted), Cord serum to maternal serum, (R cm , fresh weight based) Location of the study n Median IQR n Median IQR Median IQR β-HCH 38 0.63 (0.48,0.79) 38 0.39 (0.26,0.51) 0.21 (0.16,0.30) Wuhan, China [1] 28 1.00 (0.9,1.2) 0.30 (0.2,0.5) San Francisco, USA [11] 73 0.76 (0.50,1.07) 75 0.25 (0.16,0.33) 0.22 (0.15,0.37) Shanghai, China [3] 247 0.70 (0.46,0.94) 48 0.61 (0.36,0.86) 0.34 (0.23,0.46) Spain [8] 147 0.83 a Korea [12] p,p'- DDE 50 1.07 (0.95,1.19) 48 0.48 (0.29,0.77) 0.38 (0.33,0.48) Wuhan, China [1] 62 1.10 (1.0,1.3) 0.40 (0.3,0.5) San Francisco, USA [11] …”
Section: Datamentioning
confidence: 99%